A (in)justiça social em uma escola pública de ensino médio em Santa Maria/RS: o que os/as jovens dizem? - Minussi, Valéria Pereira (2023)
This thesis is linked to the line of research on public educational policies, educational practices and their interfaces of the Postgraduate Program in Education of the Federal University of Santa Maria. It had a research problem: in what way are the processes of social (in)justice experienced by young people in the public high schools of Santa Maria/RS?. The general objective was "to analyze the processes of social (in)justice experienced by young people from a public high school in Santa Maria/RS", with the following specific objectives: To verify the presence of social justice approaches in public policies in education; Identify the profile of young people in a public high school in Santa Maria; Verify the presence of social (in)justice cases in a public high school; Understand young people's conceptions about (In)Social Justice and its relationship with education. This was a qualitative approach investigation that carried out a documentary research and a case study on the processes of social (in)justice experienced by high school youth, having as an instrument data survey, besides documentary research, the use of questionnaire. The thesis has as categories: high school, youth and youth conditions and social justice and their approaches to redistribution, recognition, participation and justice as equality. Theoretical support included Rawls (2000a, 2000b, 2003), Fraser (2002; 2006), Nussbaum (2013; 2015), Connell (2006), Brandão (2010), Silva (2016), Abramo (2005), Margulis and Urresti (2000), among others, Also taking as a theoretical subsidy some legal documents that guide brazilian education. From this research we defend the thesis that the processes of social (in)justice pass through the day to day of the students, transcending the school context, directly influencing it from small movements and actions like the right and access to education itself, the recognition of the cultures of these young people by the school, making them feel belonging to this place, context and reality and the processes of participation, which are still clearly little explored by the school community. These approaches to social justice can be developed and improved from a democratic education, proposed by Nussbaum (2015) and liberating, proposed by Freire (2011) considering curricular justice through the look of the cultures of disadvantaged groups, in building a counter-hegemonic curriculum, which is proposed by Connell (2006).